2017
DOI: 10.3945/ajcn.116.137497
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and peripheral arterial disease incidence in middle-aged adults: the Atherosclerosis Risk in Communities (ARIC) Study ,

Abstract: Background: Peripheral arterial disease (PAD) is a costly source of morbidity and mortality among older persons in the United States. Dietary intake plays a role in the development of atherosclerotic cardiovascular disease; however, few studies have examined the relation of food intake or dietary patterns with PAD. Objective: We examined the relation between habitual dietary intake at midlife and incident PAD over w20 y of follow-up. Design: Among 14,082 participants enrolled in the ARIC (Atherosclerosis Risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 57 publications
2
22
1
Order By: Relevance
“…Lower risk of Coronary heart disease Lightly reduced risk for coronary heart disease was observed, with the lowest risk in the group consuming 2-3 cups per day1 [108][109][110][111] Coffee consumption is associated with a reduced risk of gallbladder cancer Mediated via reduced gallstone formation or through other mechanisms such as reduction of oxidative damage and inflammation and regulation of DNA repair, phase II enzymatic activity, apoptosis, angiogenesis, and metastasis [83] Table 3: Summary of health benefits of coffee consumption.…”
Section: Health Benefit Of Coffee Consumption Description Of Action Smentioning
confidence: 99%
“…Lower risk of Coronary heart disease Lightly reduced risk for coronary heart disease was observed, with the lowest risk in the group consuming 2-3 cups per day1 [108][109][110][111] Coffee consumption is associated with a reduced risk of gallbladder cancer Mediated via reduced gallstone formation or through other mechanisms such as reduction of oxidative damage and inflammation and regulation of DNA repair, phase II enzymatic activity, apoptosis, angiogenesis, and metastasis [83] Table 3: Summary of health benefits of coffee consumption.…”
Section: Health Benefit Of Coffee Consumption Description Of Action Smentioning
confidence: 99%
“…Nevertheless, we observed a significant difference in alcohol intake between patients with severe periodontitis and those with gingivitis. Alcohol consumption was the only parameter presenting a significant positive correlation with PD severity and has previously been shown to negatively affect PD (37) and to increase the risk for PAD (17,38) .…”
Section: Impact Of Periodontal Disease Severity On Dietary Intake Andmentioning
confidence: 87%
“…PD severity and patients' median number of teeth (18,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) did not correlate with other investigated nutritional parameters and FFI. The FFI indicated no difference in diet quality among the PD stages.…”
Section: Impact Of Periodontal Disease Severity On Dietary Intake Andmentioning
confidence: 88%
“…11 The association between dietary intake and PAD has been evaluated in a recent analysis from the Atherosclerosis Risk in Communities (ARIC) study, a prospective cohort study. 12 Authors found that greater meat consumption was associated with a higher risk, and moderate alcohol consumption was associated with a lower risk of incident PAD. They concluded that whether these associations are causal remains to be seen.…”
Section: Discussionmentioning
confidence: 99%